Nanoparticulate vacuolar ATPase blocker exhibits potent host-targeted antiviral activity against feline coronavirus. Issue 1 (December 2017) - Hu, Che-Ming; Chang, Wei-Shan; Fang, Zih-Syun; Chen, You-Ting; Wang, Wen-Lin; Tsai, Hsiao-Han; Chueh, Ling-Ling; Takano, Tomomi; Hohdatsu, Tsutomu; Chen, Hui-Wen
Abstract Feline infectious peritonitis (FIP), caused by a mutated feline coronavirus, is one of the most serious and fatal viral diseases in cats. The disease remains incurable, and there is no effective vaccine available. In light of the pathogenic mechanism of feline coronavirus that relies on endosomal acidification for cytoplasmic entry, a novel vacuolar ATPase blocker, diphyllin, and its nanoformulation are herein investigated for their antiviral activity against the type II feline infectious peritonitis virus (FIPV). Experimental results show that diphyllin dose-dependently inhibits endosomal acidification in fcwf-4 cells, alters the cellular susceptibility to FIPV, and inhibits the downstream virus replication. In addition, diphyllin delivered by polymeric nanoparticles consisting of poly(ethylene glycol)-block-poly(lactide-co-glycolide) (PEG-PLGA) further demonstrates an improved safety profile and enhanced inhibitory activity against FIPV. In anin vitro model of antibody-dependent enhancement of FIPV infection, diphyllin nanoparticles showed a prominent antiviral effect against the feline coronavirus. In addition, the diphyllin nanoparticles were well tolerated in mice following high-dose intravenous administration. This study highlights the therapeutic potential of diphyllin and its nanoformulation for the treatment of FIP.